Efek Anti Inflamasi Ekstrak Daun Binahong [Anredera cordifolia (Ten.) Steenis] Topikal terhadap Jumlah PMN Neutrofil pada Tikus Jantan Sprague Dawley - Gita Susanti (Jurnal Kesehatan, 2017)
The purpose of this study was to determine the efficacy of binahong leaf extract ointment topically in a new incision wound healing compared to povidone iodine ointment. An experimental study was in vivo and was carried out using pre- and post-test group design from March to April 2015. The subject of the study was 30 Sprague Dawley White Male Rats divided into 5 groups. Group 1 was given base ointment, group 2 was given povidone iodine ointment, group 3 was given binahong leaf extract ointment 10%, group 4 was given binahong leaf extract ointment 20%, group 5 was given binahong leaf extract ointment 40%. The ointment was given 4 hours after incisions. The study data were tested with Levene Test, paired sample t-test, independent t-test, one-way ANOVA, and Post Hoc test using SPSS program version 20. The average concentrate of neutrophils before and after treatment with paired sample t-test showed a significant difference (p<0.05). Effectivity test between groups with independent t-test showed a significant difference except on a positive control group and binahong leaf extract 40%, Post Hoc test showed that there was a significant difference between applying binahong leaf extract ointment and povidone iodine ointment. In conclusion, binahong leaf extract ointment 40% has an anti-inflammatory effect in decreasing 81.25% of PMN neutrophil on incision wound but it less than povidone iodine ointment in decreasing 84.64% of PMN neutrophil.